A Pliocene mekosuchine (Eusuchia: Crocodilia) from the Lake Eyre Basin of South Australia. Issue 1 (2nd January 2017) - Yates, Adam M.; Pledge, Neville S.
ABSTRACT: A new genus and species of crocodilian, Kalthifrons aurivellensis, is described from a channel sand deposit incised into the Oligo-Miocene Etadunna Formation on the western shore of Lake Palankarinna in the Lake Eyre Basin, South Australia. The channel sand is interpreted as an outcrop of the Mampuwordu Sand Member of the Tirari Formation, which has been assigned an early Pliocene age. The taxon can be diagnosed by the extremely elongate and narrow anterior process of the frontal pair and a distinctively beveled and laterally expanded prefrontal contribution to the orbit margin. The broadly triangular rostrum, at least partially interlocking dentition, smooth dental carinae, and weak labiolingual compression resemble unspecialized crocodilian species, and it was probably a generalist aquatic predator. It possessed character states that indicate that it was not a member of Crocodylus, and it is referred to the endemic Australasian clade Mekosuchinae. The first overlying unit in the Lake Eyre Basin sequence to produce diagnostic crocodilian remains is the mid- to late Pliocene Pompapillina Member of the Tirari Formation. It contains a true species of Crocodylus but no indication of Kalthifrons aurivellensis or indeed any other mekosuchine, indicating that the latter may have been driven to extinction via competitive replacement. http://zoobank.org/urn:lsid:zoobank.org:pub:C4E93358-D80F-4E4D-B7FF-BFFB93EDCD54 SUPPLEMENTAL DATA—Supplemental materials are available for this article for free atwww.tandfonline.com/UJVP Citation for this article: Yates, A. M., and N. S. Pledge. 2016. A Pliocene mekosuchine (Eusuchia: Crocodilia) from the Lake Eyre Basin of South Australia. Journal of Vertebrate Paleontology. DOI: 10.1080/02724634.2017.1244540.